Analisis Manajemen Pemenuhan Pelanggan pada Industri Kecil Menengah Pembuatan Tas dan Bordir Menggunakan Pemodelan System Dynamics (Studi Kasus pada CV. Kurnia Jaya – Yogyakarta) - Rahmanto, Nurdin; Hartono, Budi; Tontowi, Alva Edy (Jurnal Manajemen dan Organisasi, 2011)
Small Medium Enterprise (SME) plays a strategic role in developing countries economy. Each of SMEs has unique strategy of order fulfillment management. This is influenced by factor dynamics influencing the system. The system characteristic becomes the inspiration to be studied furthermore continues especially using system dynamics modeling approach. System dynamics modeling approach used because this method used to know and learn the system behavior. This paper represents of order fulfillment management analysis with case study at CV. Kurnia Jaya – Yogyakarta. The developed model has 4 sub models: customer order sub model, order fulfillment sub model, raw material management sub model and labor sub model. Next step is calibrating the developed model with boundary adequacy test, extreme conditions test and behavior reproduction test. After passing all these steps, the developed model to be ran with policy design (different scenario of order such as: constant order, step order, impulse order and actual order). Finally 3 alternative recommendations proposed for increasing the production rate so the order backlog and delivery delay decrease.